1991
DOI: 10.1002/jcp.1041460212
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns in the antioxidant defenses of the housefly, Musca domestica

Abstract: The activities of superoxide dismutase (SOD), catalase, glutathione peroxidase, glutathione S-transferases, GSSG reductase, thiol transferases, gamma glutamylcysteine synthetase, and glucose-6-phosphate dehydrogenase, and the concentrations of H2O2 and reduced and oxidized glutathione were determined in the various developmental stages of houseflies. Housefly development was correlated with a progressive increase of cellular oxidizing equivalents and a loss of cellular reducing capacity. The loss of reducing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Thus, in the present study, the second peak observed with respect to both the Hessian fly CATs in late third larval instars could address this cooperative function of ecdysteroids and CATs. These results are in corroboration with the hypothesis that during development the cellular environment gradually becomes more prone to the process of oxidation (31).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, in the present study, the second peak observed with respect to both the Hessian fly CATs in late third larval instars could address this cooperative function of ecdysteroids and CATs. These results are in corroboration with the hypothesis that during development the cellular environment gradually becomes more prone to the process of oxidation (31).…”
Section: Discussionsupporting
confidence: 90%
“…These ROS spikes could then impact specific developmental events via redox sensitive intermediates. Similar AOE disparities have been noted in Musca domestica (Allen et al, 1991).…”
Section: Discussionsupporting
confidence: 65%
“…This finding was further extended by RNA gel analysis conducted by Orr et al, (1996), who showed that mRNA levels exhibited a similar pattern. It has been postulated that such variations could impact redox levels and perhaps even play an active role in differentiation (Allen et al, 1991). In view of the critical functions that catalase may play, a more rigorous elucidation of its various roles is called for.…”
Section: Introductionmentioning
confidence: 99%